Digital Character Development, 2nd Edition - O'Neill, Rob (A K Peters/CRC Press, 2015)
Digital characters are a driving force in the entertainment industry today. Every animated film and video game production spends a large percentage of its resources and time on advancing the quality of the digital characters inhabiting the world being created. This book presents the theory and practice behind the creation of digital characters for.